To dimerize or not: para-aminothiophenol on a bismuth heterostructure - Bhadoria P.; Saroj A.; Ramanathan V. (My University, 2025)
Surface enhanced Raman spectroscopy (SERS) of p-aminothiophenol (PATP) was investigated on β-Bi2O3/Bi2O2CO3 nanoparticles, a novel bismuth based metal substrate with the lowest limit of detection of 1 mM. Unlike on noble metal surfaces where PATP gets converted to p,p′-dimercaptoazobenzene (DMAB) due to photocatalytic coupling, no such transformation of PATP was observed on β-Bi2O3/Bi2O2CO3 nanoparticles. Density functional theory (DFT) calculations at the PW91PW91/LANL2DZ/6-311+G(d,p) level of theory supported the experimental results exceedingly well. Also, the charge transfer direction from PATP to β-Bi2O3/Bi2O2CO3 nanoparticles was revealed by the projected density of states calculation. © 2023 The Royal Society of Chemistry.